Conceptual Estimation Program Construction Costs and Material Needs - Paikun Paikun (Nusa Putra University, 2019)
The construction of simple houses is always done, to meet the needs of low and middle-income people. And every time you make a home, it requires a fee to buy materials, equipment and to pay workers. So estimating the cost and material requirements at an early stage is very important. But, there is no simple cost and material estimation method, at the conceptual stage, when there is very little data information, so this is a problem for non-professionals. The solution to the problem is a theory. The theory is a program which consists of models. So this study intends to create a program, as a conceptual estimate. The quantitative method in this study uses 36 data on the Budget Plan. The data is processed using the Burgerlijke Openbare Werken (BOW) method. Then the results of the data process were analyzed using the linear regression analysis method, to get the model. The models then form the formula for the program. So that in this study produce models and applications, to estimate the cost and material requirements for the construction of simple houses. Using the program, enter the building area data information, and automatically, the cost and material requirements for the development of a simple house will be predictable. This program is a simplification of the Burgerlijke Openbare Werken (BOW) method.